The spacedog cometh - Marciano, Johnny; Chenoweth, Emily (Marciano, Johnny. Klawde (Series), 2019)
"Klawde is not your basic cat. He's an emperor from another planet, exiled to Earth. He's cruel. He's cunning. He's brilliant... and he's also Raj Banerjee's best friend. Klawde faces a challenger he never imagined: a dog, who has arrived on Earth to settle the intergalactic score. He's hyper, he's loyal, he's an all-around-good boy, and he's here to bring Klawde to justice. Can our ferocious feline evade the long paw of the law? Raj, on the other hand, is faced with his own out-of-town visitor who, although from Earth, may prove to be even more formidable: his grandmother. When she plans a birthday party Raj doesn't want, will he survive the embarrassment?"--Page [4] of cover.